Eksplorasi Etnomatematika Pada Masjid Raya Al-A’zhom Kota Tangerang - Devie Nursaidah Putri; W. Wahidin (Universitas Sarjanawiyata Tamansiswa, 2023)
Ethnomathematics is a form of mathematics learning that connects cultural history with mathematics. In this study, Masjid Raya Al-A'zhom became part of a religious culture in the City of Tangerang. The aim of this study is to further examine the cultural and mathematical concepts that exist in the building of the Masjid Raya Al-A'zhom. The research used a qualitative approach with ethnographic methods. Data were collected through primary sources, namely interviews, observations, documents, and documentation. The results of the study show that the culture applied to the construction of the Masjid Raya Al-A’zhom is Middle Eastern and Tangerang. In addition, there are several mathematical concepts in the building of the Masjid Raya Al- A’zhom, including spatial geometry, arithmetic sequences and series, geometric transformations, triple integrals in spherical coordinates, and the intersection of two circles. Ethnomathematics can improve understanding of mathematical concepts through objects that are seen in real terms, namely mosque buildings.